Stool‐Test Positivity Proportion and Five‐Year Trend of Intestinal Parasitic Infections Among Symptomatic Students Attending Debre Tabor University Student Clinic, Northwest Ethiopia: A Retrospective Cross‐Sectional Study (2021–2025) - Getu Abeje; Desalegn Abebe; Ayenew Berhan; Ayenew Asefa; Andargachew Almaw; Mulat Erkihun; Yehunie Yerdaw; Dessie Tegegne; Bekele Sharew; Teklehaimanot Kiros; Shewaneh Damtie; Seble Worku; et al. (Health Science Reports, 2026)
ABSTRACT Background and Aims Intestinal parasitic infections (IPIs) remain a significant public health challenge in Ethiopia, particularly among university students living in communal settings. However, limited data exist on the trends of these infections among university students. This study aimed to assess the 5‐year stool‐test positivity proportion and trends of IPIs among symptomatic students attending the Debre Tabor University student clinic. Methods A retrospective cross‐sectional study was conducted using data extracted from laboratory registration books at the DTU student clinic from 2021 to 2025. A total of 7778 saline wet‐mount stool examination records from students suspected of IPIs were reviewed. Data were analyzed using SPSS version 25. Descriptive statistics were computed, and the chi‐square test was used to compare infection rates between genders. All confidence intervals were calculated using the exact Clopper‐Pearson binomial method. Results A total of 7778 stool examination records were reviewed. Of these, 189 records were excluded due to incomplete data, and 7589 records were included in the final analysis. The overall stool‐test positivity for intestinal parasites among symptomatic clinic attendees was 30.3% (2299/7589; 95% CI: 29.3–31.3). Protozoan infections accounted for 28.8% (2187/7589; 95% CI: 27.8–29.8), while helminthic infections were less common at 1.5% (112/7589; 95% CI: 1.2–1.8). Entamoeba histolytica/dispar was the most prevalent parasite (15.8%; 1201/7589; 95% CI: 14.9–16.7), followed by Giardia lamblia (12.8%; 966/7589; 95% CI: 12.0–13.6). Annual positivity rates ranged from 27.4% (2024) to 31.6% (2021), but the Cochran‐Armitage test for trend showed no statistically significant linear trend ( Z = −0.89, p = 0.37). Conclusion This study identified a substantial stool‐test positivity proportion (30.3%) among symptomatic students attending the DTU student clinic for suspected IPIs. E. histolytica/dispar and G. lamblia were the predominant parasites identified. These findings highlight the need for improved sanitation infrastructure, health education, and targeted screening programs for students presenting with gastrointestinal symptoms.